PENGARUH HARGA DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA GRAMEDIA GAJAH MADA MEDAN - Siagian, Sarah Nabila; Adlina, Hafiza (Transpublika Publisher, 2023)
Gramedia, a thriving retail establishment specializing in books and office supplies, serves as the focal point of this study. Examining the effects of pricing and in-store atmosphere on consumer decision-making at the Gramedia Gajah Mada Medan branch is the study's main goal. We will delve into the implications of price on individuals and society as a whole and store ambiance on purchasing choices. The findings unveiled that the pricing factor (X1) exerts an insignificant influence on purchasing decisions. In contrast, the store's ambiance factor (X2) exerts a substantial impact on consumer choices. When evaluated in tandem, both pricing and store ambiance factors collectively influence purchasing decisions (Y). The coefficient of determination analysis, characterized by an R2 value of 0.608 or 60.8%, illuminates that pricing and store ambiance factors can account for 60.8% of variations in the purchasing decision variable. The remaining 39.2% is subject to the sway of other variables such as service quality, location, or other unexplored factors outside the purview of this study.